Development of Islamic Economy and Finance in Indonesia through KNEKS Structure in 2019-2024 - Robbani, Teuku Muhammad Fauzan; Mukhlis, Madian Muhammad (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2024)
This research discusses the development of Sharia Economics and Finance in Indonesia through the KNEKS Structure in 2019-2024. This research discusses the Direction of Development and Strengthening of Sharia Economics and Finance in Indonesia, of course strengthening the halal value chain with a focus on sectors or clusters that are considered potential and highly competitive; second, strengthening the sharia financial sector whose master plan has been outlined in the Indonesian Sharia Financial Architecture Masterplan or AKSI which has been refined in this master plan; third, strengthening micro, small and medium enterprises or MSMEs as the main drivers of the halal value chain. For the research process on Sharia Economic and Financial Development in Indonesia Through the KNEKS Structure in 2019-2024, this research used the library research method, and we conducted this research where the data study object used library data sourced from several types of books and the internet. as a source for obtaining these data. Then we read, study and understand various kinds of literature related to the research we are doing. And we also use a qualitative observation method by observing data sourced from a book entitled sharia economics, especially at the undergraduate level of higher education. This research is also useful for knowing the direction of development and strengthening of sharia economics and finance in Indonesia through the KNEKS structure in 2019-2024.